Theory & Design of Air Cushion Craft. - Yun, Liang (Elsevier, 2000)
This definitive text describes the theory and design both of Air Cushion Vehicles (ACV) and Surface Effect Ships (SES). It begins by introducing hovercraft types and their development and application throughout the world in the last three decades, before going on to discuss the theoretical aspects of ACV and SES craft covering their hovering performance, dynamic trim over calm water, resistance, stability, manoeuvrability, skirt configuration and analysis of forces acting on the skirts, ACV and SES seakeeping, and the methodology of scaling aerodynamic and hydrodynamic forces acting on the ACV.